Penggunaan limbah organik cair pabrik kelapa sawit dan industri tahu dalam meningkatkan kualitas fisikokimia dan stok karbon tanah haplustepts - Khusrizal; Nasruddin; Muliana; Olivia Sukma Zein; Nita Erliana (Jurnal Ilmiah Pertanian, 2022)
The soil type of Haplustepts found in Reuleut, Aceh Utara, possessed low fertility. However, it still has potential for agriculture development through organic matter application, both solid and liquid, to improve its soil qualities. The objective of this study is to examine the effect of the Palm Oil Mill Effluent (POME) and Tofu Industry Liquid Waste (TOFU) on the changes in soil physicochemical properties and soil organic carbon stock (SOCs) of Haplustepts. The study was designed using a Factorial Randomized Block Design, comprising two factors and three replications. The first factor was POME with three different doses: S0 (0 L/27,000 cm3 of soil volume), S1 (1.62 L/27,000 cm3 of soil volume), and S2 (3.24 L/27,000 cm3 of soil volume). The second factor was TOFU comprising three different doses: T0 (0 L/27,000 cm3 of soil volume), T1 (2.7 L/27,000 cm3 of soil volume), and T2 (5.4 L/27,000 cm3 of soil volume). The results indicated that different doses of POME and TOFU applied were non-significant on soil aggregate, bulk density, and soil water availability in Haplustepts. Similar results were recorded on organic-C content, soil pH, cation exchange capacity (CEC), and SOCs. Although insignificant, the value of soil aggregate stability and SOCs increased as the doses of POME and TOFU increased. The indicators of these insignificant results were the different doses applied, high soil water content, and a short period of POME and TOFU incubation.